Distinct role of hydrodynamic shear in leukocyte-facilitated tumor cell extravasation - Slattery, Margaret J. (2004)
Previously, we found polymorphonuclear neutrophils (PMNs) increased melanoma cell extravasation under flow conditions (Intl J Cancer 106: 713–722, 2003). In this study, we characterized the effect of hydrodynamic shear on PMN-facilitated melanoma extravasation using a novel flow-migration assay. The effect of shear stress and shear rate on PMN-facilitated melanoma extravasation was studied by increasing the medium viscosity with dextran to increase shear stress independently of shear rate. Under fixed shear rate conditions, melanoma cell extravasation did not change significantly. In contrast, the extravasation level increased at a fixed shear stress but with a decreasing shear rate. PMN-melanoma aggregation and adhesion to the endothelium via β(2)-integrin/intracellular adhesion molecule-1 (ICAM-1) interactions were also studied. Lymphocyte function-associated molecule-1 (LFA-1; CD11a/CD18) influenced the capture phase of PMN binding to both melanoma cells and the endothelium, whereas Mac-1 (CD11b/CD18) affected prolonged PMN-melanoma aggregation. Blockage of E-selectin or ICAM-1 on the endothelium or ICAM-1 on the melanoma surface reduced PMN-facilitated melanoma extravasation. We have found PMN-melanoma adhesion is correlated with the inverse of shear rate, whereas the PMN-endothelial adhesion correlated with shear stress. Interleukin-8 (IL-8) also influenced PMN-melanoma cell adhesion. Functional blocking of the PMN IL-8 receptors, CXCR1 and CXCR2, decreased the level of Mac-1 upregulation on PMNs while in contact with melanoma cells and reduced melanoma extravasation. We have found PMN-facilitated melanoma adhesion to be a complex multistep process that is regulated by both microfluid mechanics and biology.